Solutions of fractional-stochastic Bao's system - İnç, Mustafa; Akinlar, M. A.; Tchier, F.; Bal, C.; Bousbahi, F.; Tawfiq, F. M. O.; Weber, G. W. (Elsevier, 2020)
Systems of high-dimensional nonlinear ordinary differential equations play a significant role in Physics and applied sciences including big-data optimization, financial models, epidemic disease models. In this paper, we are concerned with numerical solutions of Bao's system that is a 4-dimensional hyperchaotic system introduced by Bo-Cheng and Zhong (2008). We solve the Bao's system with both the Crank-Nicolson and power series methods. Crank-Nicolson method is eventually evolved into a new system whose solution is presented in a quite neat algorithmic manner. By adding standard Brownian motion to each term in the model, we express the Bao's system as a system of stochastic differential equations. We solve the stochastic system with an Euler-type approximate solution method. By adding noise and expressing time derivatives with Caputo-type fractional derivative, we study on synchronization and parameter estimation of the models. To the best of our knowledge, Bao's system has not been numerically solved with the methods employed in this paper previously, and this paper considers fractional and stochastic Bao's system for the first time in the history of research. Techniques employed by us in this paper may serve as a framework for solutions of many other systems of ordinary differential equations including Lorenz types and epidemic models. (C) 2020 The Authors. Published by Elsevier B.V. on behalf of Faculty of Engineering, Alexandria University.
Keywords: Fractional and stochastic; Bao system; Crank-Nicolson and power; series methods; Numerical solution